Field Environmental Philosophy: A Biocultural Ethic Approach to Education and Ecotourism for Sustainability - Tauro, Alejandra; Ojeda Villarroel, Jaime Andrés; Caviness, Terrance; Moses, Kelli P.; Moreno-Terrazas, Rene; Wright, T.; Zhu, Danqiong; Poole, Alexandria K.; Massardo Vega, Cristina Elvira Francisca; Rozzi Marin, Ricardo Roberto (My University, 2021)
To contribute to achieving local and global sustainability, we propose a novel educational methodology, called field environmental philosophy (FEP), which orients ecotourism practices to reconnect citizens and nature. FEP is based on the systemic approach of the biocultural ethic that values the vital links among the life habits of co-inhabitants (humans and other-than-humans) who share a common habitat. Based on this "3Hs" model (habitats, co-inhabitants, habits), FEP combines tourism with experiential education to reorient biocultural homogenization toward biocultural conservation. FEP's methodological approach seeks to integrate social, economic, and environmental dimensions of sustainability by generating new links between biological and cultural diversity at different spatial and social scales. Ecotourism has an underutilized potential to link sciences with education and conservation practices at different scales. By incorporating a philosophical foundation, FEP broadens both understanding and practices of environmental education and sustainable tourism. FEP has been developed at the Omora Ethnobotanical Park in the Cape Horn Biosphere Reserve, Chile, at the southern end of the Americas since 2000, where it has oriented transdisciplinary work for the creation of new protected areas and ecotourism practices. FEP enables an integration of biophysical, cultural, and institutional dimensions into the design of ecotourism activities that transform and broaden the perceptions of tourists, local guides, students, and other participants to better appreciate local biological and cultural diversity. FEP's methodology is starting to be adapted in other world regions, such as Germany, Japan, and Mexico, to integrate education and ecotourism for sustainability.
Keywords: biocultural conservation; biodiversity; cape horn biosphere reserve; chile; ethics; metaphors; tourism